2020
DOI: 10.1002/jdd.12423
|View full text |Cite
|
Sign up to set email alerts
|

Nigerian undergraduate dental students’ knowledge, perception, and attitude to COVID‐19 and infection control practices

Abstract: Purpose/objectives The current coronavirus disease 19 (COVID‐19) pandemic has affected most countries. Infection, Prevention, and Control training is important in mitigating the spread of COVID‐19. The closure of universities by the Nigerian government has hampered academic activities of dental students. Our objectives were to assess the knowledge, perception, and attitude of undergraduate dental students in Nigeria to the COVID‐19 pandemic and infection control practices. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
53
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(76 citation statements)
references
References 10 publications
7
53
1
5
Order By: Relevance
“…The included studies were all conducted in sub-Saharan Africa and published in 2020. Ten of the studies were conducted in Ethiopia [10,12,[29][30][31][32][33][34][35][36], eight in Nigeria [37][38][39][40][41][42][43][44], three in Cameroon [45][46][47], two in Uganda [9,48], one each in Rwanda [49], Ghana [50], Democratic Republic of Congo [51], Sudan [52], and Sierra Leone [53], (Fig 2). A total number of 14,353 study participants were reported in the included studies, with over half (51%) of them being males.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The included studies were all conducted in sub-Saharan Africa and published in 2020. Ten of the studies were conducted in Ethiopia [10,12,[29][30][31][32][33][34][35][36], eight in Nigeria [37][38][39][40][41][42][43][44], three in Cameroon [45][46][47], two in Uganda [9,48], one each in Rwanda [49], Ghana [50], Democratic Republic of Congo [51], Sudan [52], and Sierra Leone [53], (Fig 2). A total number of 14,353 study participants were reported in the included studies, with over half (51%) of them being males.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Good preventative practice towards COVID-19 was found in twelve studies [9, 30, 36-38, 42, 43, 45, 46, 49, 50, 52], average in six [10,12,29,39,48,53], and low in other six studies [31-33, 35, 47, 51]. Thirteen of the included studies were from the Eastern African region of SSA, with Ethiopia [10,12,[29][30][31][32][33][34][35][36], Uganda [9,48] and Rwanda [49] accounting for ten, two and one, respectively, whereas West Africa contributed ten studies, with eight being from Nigeria [37][38][39][40][41][42][43][44], one from Ghana [50], and one from Sierra Leone [53]. A total of four studies were from the Central Africa, with one and three representing the Democratic Republic of Congo [51], and Cameroon [45][46][47], respectively.…”
Section: Plos Onementioning
confidence: 99%
See 2 more Smart Citations
“…A study by Umeizudike et al 29) emphasized that wearing face masks, gloves, and face shields during dental procedures could prevent COVID-19 transmission. Wearing a face mask alone reduces the risk of airborne infections in healthy people but provides insufficient protection from airborne viruses 30) .…”
Section: Characteristics Of Studies Included In the Reviewmentioning
confidence: 99%